2014
DOI: 10.1016/j.jcmg.2013.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Disease in Patients With Human Immunodeficiency Virus Infection

Abstract: With advances in antiretroviral therapy, individuals with human immunodeficiency virus (HIV) infection are living longer and increasingly die of non-HIV related diseases such as cardiovascular disease (CVD). Several observational studies suggest that HIV-infected patients on ART are at increased CVD risk; however, the precise mechanisms underlying the association between HIV infection and CVD risk are uncertain. Atherosclerosis and arterial disease in HIV-infected individuals is a multifactorial process with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 75 publications
(109 reference statements)
2
52
1
2
Order By: Relevance
“…It is unclear whether differences in ART regimens or their metabolic effects influence CVD risk, in large part because few randomized clinical trials assessing ART have had a significant number of adverse CVD events due to the young age of the participants and short duration of follow-up [1]. Thus, evaluating the effects of ART on surrogate endpoints that predict adverse CVD events is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unclear whether differences in ART regimens or their metabolic effects influence CVD risk, in large part because few randomized clinical trials assessing ART have had a significant number of adverse CVD events due to the young age of the participants and short duration of follow-up [1]. Thus, evaluating the effects of ART on surrogate endpoints that predict adverse CVD events is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The relative contributions of antiretroviral therapy (ART), traditional cardiovascular disease (CVD) risk factors, inflammation, and immune activation on arterial injury and atherosclerosis progression in HIV-infected individuals are not known [1]. Previous observational studies, including studies of carotid intima-media thickness (IMT), have suggested that patients with HIV infection are at increased risk for CVD [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A review by Stein et al suggested the increased use of non-invasive imaging studies including carotid ultrasound, CAC, arterial inflammatory imaging using PET, and brachial artery reactivity testing for monitoring of CHD risk in HIV-infected patients. 20 Mechanisms by which HIV increases cardiovascular risk include: ART metabolic dysfunction caused by ART, 3 and a chronic inflammatory state, particularly in the vasculature, caused by HIV. Individuals with HIV are also more likely to be smokers or have smoked cigarettes, and have higher rates of other traditional risk factors such as dyslipidemia and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The WG noted that HIV might alter and potentially accelerate the natural history of the fundamental processes underlying atherosclerosis, endothelial dysfunction, and thrombosis (3445). The participants also observed that the mechanisms by which HIV and ART may modify these processes have still not been fully elucidated.…”
Section: Resultsmentioning
confidence: 99%